2020
DOI: 10.1021/acs.jpcc.0c00517
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Property Correlation Study for Organic Photovoltaic Polymer Materials Using Data Science Approach

Abstract: A study workflow that utilizes several data science methods to apply on polymer materials databases is introduced to reveal correlations among their properties, structural information, and molecular descriptors. The data science methods used in this pipeline include the unsupervised machine learning (ML) method of self-organizing mapping (SOM) and the polymer molecular descriptor generator, both of which have been tailored to fit the polymer materials study. To demonstrate how this pipeline can be applied in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Moreover, ML algorithms can instantaneously give an answer by considering big data, which is impossible for human brains. Thus, ML‐based studies are being conducted in different areas such as a lithium‐ion batteries, [ 6–8 ] thermoelectronics, [ 9–11 ] organic light‐emitting diodes, [ 12–14 ] organic photovoltaics (OPV), [ 15–33 ] and organic‐inorganic hybrid perovskite solar cells. [ 34–41 ]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ML algorithms can instantaneously give an answer by considering big data, which is impossible for human brains. Thus, ML‐based studies are being conducted in different areas such as a lithium‐ion batteries, [ 6–8 ] thermoelectronics, [ 9–11 ] organic light‐emitting diodes, [ 12–14 ] organic photovoltaics (OPV), [ 15–33 ] and organic‐inorganic hybrid perovskite solar cells. [ 34–41 ]…”
Section: Introductionmentioning
confidence: 99%
“…[163][164][165][166] We also note that the use of computer-aided approaches should be widely extended to accelerate the understanding of the structuremorphology-performance relationship of OPV materials. There have been already several studies in this context, [167][168][169][170][171][172][173] and research efforts in this area will aid achieving PCEs nearing the theoretical limit.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the way ML methods are conceived, they are unlikely to provide guidance on the maximum achievable performance on each technological domain as in the examples presented in Section 4.d but they can be very powerful in discovering novel correlations and ranking the importance of the features included in any model in particular with the advances of explainable ML. 439 For example, recent studies have showed how ML can be a fast and efficient way to select effective molecular features correlated with the PCE of polymer materials, 444 and can be used to rationalise the effects that the feature's trends have on the open-circuit voltage ( V OC ), short-circuit current ( J SC ) and fill factor (FF) of OPVs. 435 …”
Section: Discussionmentioning
confidence: 99%